Evaluation of Ventricular Remodeling and Prognosis in Patients with Aortic Stenosis Who Underwent Surgical or Percutaneous Transcatheter Aortic Valve Replacement - Joaquim,Rodrigo de Moura (2022)
ABSTRACT Introduction: Aortic stenosis is the most common heart valve disease in the world, and patients that present with symptoms have a high mortality rate. Aortic valve replacement has the objective of promote left ventricular remodeling, reduce symptoms, and increase overall survival. The objective of this study is to evaluate reverse remodeling of the left ventricle in patients with severe and symptomatic aortic stenosis who underwent surgical or percutaneous transcatheter aortic valve replacement. Methods: This is a longitudinal, prospective, non-concurrent, non-randomized unicentric study with patients who underwent aortic valve replacement. Echocardiogram was performed before and after replacement procedure to evaluate several remodeling indexes. Results: Of 91 patients, 77 (84.6%) underwent surgical aortic valve replacement, and 14 (15.4%) underwent percutaneous transcatheter aortic valve replacement. Mean age was 68,96±11,98 years, and most patients were male. Remodeling evaluation revealed that patients who decreased left ventricular index mass (53% vs. 38.9%; P=0,019) and those who reduced the mass/volume ratio (30.4% vs. 68.9%; P<0,001) presented with positive left ventricular remodeling. No endpoint difference was found in those with positive remodeling. Conclusion: Regarding the left ventricular remodeling in patients with severe and symptomatic aortic valve stenosis who underwent percutaneous transcatheter or surgical valve replacement, there is a positive increment in remodeling, however it remains in concentric hypertrophic shape. Implication of these findings remains uncertain and to be studied in large dedicated trials with clinical endpoints.